Pengaruh Kombinasi Aromaterapi Lemon Dan Akupresur Terhadap Penurunan Mual dan Muntah Pada Ibu Hamil Trimester I di Praktek Mandiri Bidan Suryati Kabupaten Jayapura - Purba, Ellen R.V; Romauli, Suryati; Rahayu, Gemi; Gultom, Elis (JURNAL WACANA KESEHATAN, 2024)
Nausea and vomiting are common symptoms experienced by pregnant women, especially in the first trimester, and can interfere with the quality of life and well-being of the mother. Although this condition is often considered normal, excessive nausea and vomiting can lead to dehydration, electrolyte imbalance, and weight loss, which is a risk to the health of the mother and fetus. The combination of lemon aromatherapy and acupressure has long been known as a non-invasive method that can help reduce nausea and vomiting. The purpose of the study was to evaluate the effect of the combination of lemon aromatherapy and acupressure on the reduction of nausea and vomiting in pregnant women in the first trimester at the Suryati Midwifery Independent Practice, Jayapura Regency. The results showed that before the intervention was given, the majority of respondents in the intervention and control groups experienced nausea and vomiting in the moderate and severe categories. After the intervention for 7 days with a frequency of 3 times a day, the intervention group experienced a significant decrease in the rate of nausea and vomiting, switching to the moderate and mild categories. In contrast, the control group that did not receive the intervention showed no significant change, with the majority remaining in the category of moderate and severe nausea and vomiting. Statistical analysis showed that there was a significant difference in the intervention group with a p-value of 0.001 (p < 0.05), while there was no significant difference in the control group (p-value 0.564). These findings confirm the effectiveness of the combination of lemon aromatherapy and acupressure as a safe and effective alternative in reducing nausea and vomiting in pregnant women in the first trimester.